THE INTERRUPTION USED IN MIXED GENDER IN INI TALK SHOW ON NET TV - DONNY JOHANNES P; SITI Aisah Ginting; Muhammad Natsir (LINGUISTICA, 2020)
Talk show is a tool of people communicates to convey the important information such as successes, or the phenomenon in society. In a talk show, they use language to start conversation between the host and the guest stars who will talk about a particular topic. Every human being communicates using different languages to achieve the purposes. In this case, the language phenomenon often occurs in a conversation. The language phenomenon often happened in conversation is interruption. Based on the background above this research investigates the interruption used by the participants in Ini Talk Show on Net TV. The objectives of this research are to identify the types and functions of interruption used by the participants in the talk show. This research used descriptive qualitative as a method. The form of the data were utterances that used by the participants in two episodes of Ini Talk Show. The researcher was the primary instrument of this research. The theories that used to analyzing the data are Ferguson (1977), Murata (1983), Kennedy and Camden (1983), Han Z. Li (2001), Zimmermen and West (1975). The result of the research, the researcher found four types of interruption used by the participants in the talk show are simple interruption (23), overlap interruption (70), butting-in interruption (7), and silent interruption (13). There were 113 data of interruption found in this research; the most type which appeared (70) times by the participants is overlap interruption, because each participant cannot wait to give his or her opinion toward the topic of the conversation. In this case, the current speaker does not give the turns before his or her finishing the utterance but the interrupter still disrupted and talk in sametime. Furthermore, two functions of interruption are found in this talk show are cooperative interruption consist of agreement (27), assistance (10), and clarification (29), while intrusive interruption divided into disagreement (3), floor taking (21), topic change (16), and tangentialization (7). The most function that appeared is clarification. Clarification appeared (29) times, the participants do interruption not only to shows the words does not understand but also to emphasizes the important words that get from the participant messages. Keywords: Conversation, Interruption, Participants, Ini Talk Show